Analysis of factors causing delays in seeking medical attention and its relationship with short-term prognosis in patient with acute ischemic stroke (急性缺血性脑卒中患者延迟就医原因与短期预后相关性分析) - PENG Hong (彭红); CHEN Xiangyang (陈向阳); ZHANG Xiuliang (张修亮) (中西医结合护理)
Objective To investigate the factors causing delays in seeking medical attention and its relationship with short-term prognosis in patient with acute ischemic stroke, and provide reference for the interventions on seeking timely medical attention. Methods Totally 131 patients with acute ischemic stroke who attended the hospital between September 2021 and August 2022 were included. The general information and clinical data of patients were retrospectively analyzed. According to the time to medical attention, those with time to medical attention more than 3. 5 h were included as the Delay group, and those with time to medical attention less than 3. 5 h were assigned to the Non-Delay group. Results There were 74 cases in the Non-Delay group and 57 cases in the Delay group. There was no significant difference in age, gender, marital status, education level, medical insurance, employment status, current place of residence, distance to hospital, type of hospital attention, place of disease onset, time to medical attention, time of disease onset, symptoms, type of disease onset, medical history and NIHSS score at hospital admission between two groups (P＞0. 05). The type of symptom identification and NIHSS score at 14th day of hospital admission in the Non-Delay group was lower than that in the Delay group(P＜0. 05). Conclusion There is a relationship between delays in seeking medical attention and type of symptom identification, which may affect the short-term prognosis in patient with acute ischemic stroke. It is required to enhance the public health education about identification of stroke signs. (目的 调查分析急性缺血性脑卒中患者院前延迟就医的原因与短期预后的相关性, 为制定促使患者院前及时就医的干预措施而提供科学依据。方法 纳入2021年9月—2022年8月就诊于医院急诊科的131例急性缺血性脑卒中患者作为研究对象。采用统一的自制调查表记录患者一般信息和临床资料。根据就诊时间, 将症状出现至就诊时间≥3. 5 h的患者设为院前延迟就医组, 时间＜3. 5h的患者设为及时就医组。采用单因素分析相关因素。结果 及时就医组患者74 例, 延迟就医组患者 57例。两组患者在年龄、性别、婚姻状况、文化程度、医疗保险、职业状态、现居住地、距离、就诊方式、发病地点、入院时间、发病时间、发病症状、发病模式、既往病史、入院时美国国立卫生研究院卒中量表(NIHSS)评分方面差异无统计学意义(P＞0. 05)。两组患者症状识别方式和发病第14天的NIHSS评分比较, 差异有统计学意义(P< 0. 05)。结论 急性缺血性脑卒中延迟就医原因与相关症状识别方式密切相关, 影响患者的短期预后, 应加强大众识别卒中相关症状的健康教育以促进患者及时就诊。)